PENGETAHUAN MAHASISWA TENTANG PROTOKOL KESEHATAN DALAM PENCEGAHAN PENYEBARAN COVID-19 DI ERA NEW NORMAL PADA PROGRAM STUDI STIKes SANTA ELISABETH MEDAN TAHUN 2021 - Rusmauli Lumbangaol; Magdalena Meylin Lasria Nainggolan (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
Coronavirus Disease 2019 (Covid-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus2 (SARS-CoV-2). The most common symptoms of Covid-19 are fever, fatigue, and a dry cough. Covid-19 is transmitted from symptomatic people to other people who are in close proximity through water-filled particles >5-10 m in diameter. Students are a young age group that has the potential to transmit the corona virus even without showing symptoms. Implementation of health protocols is important in the current new normal era. The new normal will be in line with the implementation of health protocols in daily life, if there is a neglect of health protocols, it will result in the continued increase in the number of Covid-19 cases. Objective: The study was to find out the description of students' knowledge about health protocols in preventing the risk of spreading Covid-19 in the New Normal era based on the Santa Elisabeth Medan Health College Study Program in 2021. This study used a descriptive method where data collection was carried out by distributing questionnaires of 30 statements so as to be able to find out about student knowledge about the covid-19 health protocol. The sampling technique used simple random sampling as many as 112 respondents. The results of the study of 112 respondents 105 respondents (94%) had good knowledge, 7 respondents (6%) had sufficient knowledge and 0 respondents (0%) had poor knowledge. Maintain and increase student knowledge about prevention and protocols for covid-19. Obstacles faced when conducting research, namely when giving research questionnaires, some respond and some do not respond in filling out the questionnaire.